Profissional ou professor de educação física? interfaces de uma profissão regulamentada - Sofiste, Ana Flávia Souza (2007)
The approval on September 1st, 1998 of the Law 9.696 that regulates the Physical Education Professionals and creates the Federal Council of Physical Education (CONFEF) and Regional Council of Physical Education happens in the extent of a dialogue among groups that are favorable to this arrangement among which we can point out the ones which have taken positions at CONFEF and the ones against the regulation that have been articulated around the National Movement Against the Regulation of the Physical Education Professionals (MNCR), deflagrated in the XX National Meeting of Physical Education Students in 1999, due to several meetings promoted during the Student Movement. The presence of a speech that was characterized by the defense of the regulation pros and againsts led us to consider that discussion in the extent of the quarrels in the Physical Education field, having as reference Pierre Bourdieu s concept. The nature of that discussion allowed us to take the theme of the Regulation of the Physical Education Professionals in order to analyze the social historical factors that configured the status of the ones responsible for the teaching of that subject based on António Nóvoa s studies about educational professionalization. To carry out this study, we analyzed the speeches produced in Revista Brasileira de Ciências do Esporte, published by the Brazilian School of Sciences of the Sport (CBCE) since 1979, in Revista E.F., informative instrument of CONFEF since 2001 and in Boletim do MNCR, edited since 2002. Besides, we also examined the documents produced by CONFEF with the purpose of deliberating actions that affect the organization and structuring of that organization and by MNCR, as the Manifests, the Letters and the Unconstitutionality Actions moved against CONFEF. We understood that the speeches in the debate of the Regulation of the Physical Education Professionals characterize this field that concerns the disputes for the definition of a professional identity, in which different conceptions concerning the kinds of knowledge that should support the Physical Educator's formation and the criteria for his selection confront each other, taking into consideration the different possibilities of performance